Nanoclay Reinforced Polymer Composites Nanocomposites and Bionanocomposites - Jawaid, Mohammad; Qaiss, Abou el Kacem; Bouhfid, Rachid; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book is part of a two-volume book series that reviews exhaustively the key recent research into nanoclay reinforced polymer composites. This is the second volume of the book series which focuses on nanoclay based nanocomposites and bionanocomposites fabrication, characterization and applications. This includes classification of nanoclay, chemical modification and processing techniques of nanocomposites. The book also provides comprehensive information about nanoclay modification and functionalization; modification of nanoclay systems, geological and mineralogical research on clays suitability; bio-nanocomposites based on nanoclays; modelling of mechanical behaviour of halloysite based composites; mechanical and thermal properties of halloysite nanocomposites; the effect of Nanoclays on gas barrier properties of polymers and modified nanocomposites. The book is a valuable reference guide for academics and industrial practitioners alike.
Bionanocomposites based on Nanoclays: Role of various polymers and shape of Nanoclays -- Modelling the mechanical behaviour of halloysite nanotubes reinforcing polymer-based composites -- A review of mechanical and thermal properties of halloysite nanotube (HNT) based polymer composites -- Effect of nanoclays on gas barrier properties of polymers and co-polymers nanocomposites -- Bionanocomposites based on modified montmorillonite and nanocrystaline cellulose -- Nanoclay modification and functionalization-Dr.Qaiss and dr. Rachid, Morocco -- Characteristic properties of nanoclays and characterization of nanoparticulates and nanocomposites -- Modification of Nanoclay Systems: An Approach to Explore Various Applications -- Geological and Mineralogical Research on Clays Suitables for Nanocomposite -- Hybrid Polymer layered silicate nanocomposites -- Synthesis of natural rubber/palygorskite nanocomposites via silylated and cation exchange method -- The effect of Nanoclay on the properties of tropical wood polymer nanocomposites.
Keywords: Ceramic materials; Polymers; Materials; Ceramics; Polymers; Materials Engineering